Essays in honor of Joon Y. Park : econometric theory - Chang, Yoosoon; Lee, Sokbae; Miller, J. Isaac (Emerald Publishing Limited, 2023)
Volumes 45a and 45b of Advances in Econometrics honor Joon Y. Park, Wisnewsky Professor of Human Studies and Professor of Economics at Indiana University. Professor Park has made numerous and substantive contributions to the field of econometrics since beginning his academic career in the mid-1980s and has held positions at Cornell University, University of Toronto, Seoul National University, Rice University, Texas A&M University, and Sungkyunkwan University. This first volume, Essays in Honor of Joon Y. Park: Econometric Theory, features contributions to econometric theory related to Professor Park's analysis of time series and particularly related to the research of the first two or so decades of his career.
Keywords: Econometrics.; Business & Economics -- Econometrics.; elektronické knihy; electronic books